Les artisans africains : étude sociale et organisation du travail - Touatia Amraoui (Antiquités Africaines, 2016)
The epigraphic inventory of the Latin inscriptions mentioning craftsmen discovered in Algeria allows presenting a first social study of the African artifices. The epigraphic attestations inform about the production specialties, especially in cities, as well as on craftsmen legal status, age and gender. For some of them, the role in the workshop or in the production line can be also identified more precisely. Less frequent than in Italy and in Gaul, these African monuments do not figure craftsmen. Nevertheless, archaeological data or ancient texts show that craftsmen could praise their job and their “savoir-faire” through other kinds of representation. This article appears as the first part of the results of a vaster research on African craftsman and his links of sociability.